A Postcolonial Reading of Nikolai Gogol’s Taras Bulba - Dr Ali Salami (University of Chitral Journal of Linguistics and Literature, 2020)
The sixteenth-century Cossacks became the favourite topic of Ukrainian authors of the nineteenth century who dealt with national and individual identity issues. Nikolai Gogol, the celebrated Russian author who had Ukrainian origin and was born in a Cossack village, wrote the epic romance of Taras Bulba, which narrated the story of Cossacks and their struggle for preserving their independence. While the work has been previously studied under the light of postcolonial theoretical framework, using the concepts developed by Homi Bhabha to scrutinize the situation and the destiny of the two main hybrid characters, Taras Bulba’s sons, takes a step further and reveals the deeply ingrained anxiety and ambivalence in the Cossack mentality. The article focuses on the two main hybrid characters who choose divergent paths upon encountering the conflict brought to them by the imperial power.